2023
DOI: 10.1002/ca.24021
|View full text |Cite
|
Sign up to set email alerts
|

A marginal process of the zygomatic bone predicts a lateral exit of the zygomaticotemporal nerve: An anatomical study with application to surgery around the midface

Abstract: Previous studies have not verified the contents of accessory foramina of the zygomatic bone on dry skulls and thus could not conclude whether they carried accessory zygomaticofacial nerve branches or branches or the entire trunk of the zygomaticotemporal nerve (ZTN). Therefore, the aim of the current study is to present findings from cadaveric dissections to clarify this relationship. Fifty, fresh frozen, adult cadaveric sides underwent dissection of the ZTN. When identified, these nerves were quantified and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The nerves passing within type II canals are unknown, and identifying the nerves running along these courses is of great interest. Siddiqui et al [ 38 ] recently reported that, though relatively uncommon, the ZTN can pierce the marginal process (marginal tubercle) of the zygomatic bone and can thus be located superficially to the cheek region. All ZFFs that were classified as type II in the present study were located near the posterior margin of the FPA; thus, type II canals likely harbor the ZTNs that innervate the cheek.…”
Section: Discussionmentioning
confidence: 99%
“…The nerves passing within type II canals are unknown, and identifying the nerves running along these courses is of great interest. Siddiqui et al [ 38 ] recently reported that, though relatively uncommon, the ZTN can pierce the marginal process (marginal tubercle) of the zygomatic bone and can thus be located superficially to the cheek region. All ZFFs that were classified as type II in the present study were located near the posterior margin of the FPA; thus, type II canals likely harbor the ZTNs that innervate the cheek.…”
Section: Discussionmentioning
confidence: 99%